Pemerolehan Fonologi Anak Usia 4 Tahun (Studi Kasus Anak dari Pasangan Tunawicara) - Dewi Yanti; Tiara Noviarini (Journal of Social, Culture, and Language, 2023)
The phenomenon of language acquisition is an interesting discussion. The interest in language acquisition is in the factors, both external, and internal in the process of its continuity. This study focuses on the acquisition of phonology in a 4-year-old child. The child (Ghani) in this study is the child of a speech impaired couple. The methodology used in this research is descriptive combined with case study approach. Based on the phonological acquisition data, it shows that all vowel sounds have appeared, either in the initial, middle or final position. For diphthong sounds that have not appeared are [ei] and [oi], while the bunya [ai] has not appeared in the middle position, diphthong [au] cannot be sounded in the middle and final position. In consonant sounds, there are consonants [f], [j], [k], [q], [r], [v], [x], [z] that cannot be sounded. The consonants have not been able to sound and occupy their positions, such as the consonant [b] [d] has not sounded in the initial and final positions. Consonants [g] [t] cannot be sounded in the middle position, [h] [w] [y] cannot be sounded in the middle and final position, [s] does not sound in the initial and middle position. Keywords: Keywords: Acquisition, Phonology, Child, Case Study, Speech Impaired